2018
DOI: 10.1111/bjd.17148
|View full text |Cite
|
Sign up to set email alerts
|

Local interventions for actinic keratosis in organ transplant recipients: a systematic review

Abstract: Limited evidence is available for the treatment of AKs in OTRs. MAL-PDT is currently the best-studied intervention. Lesion-specific regimens may not be sufficient to achieve disease control. Field-directed regimens are preferable in this high-risk population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 38 publications
(49 reference statements)
0
39
0
Order By: Relevance
“…About this, there are data supporting the use of PDT in the treatment of AKs in OTRs; and a recent clinical trial compares PDT with IMI 5%, showing a higher efficacy of PDT (17,18). In a recent review, PDT shows the highest rates of complete clearance (40-76.4%), followed by IMI 5% (27.5-62.1%), diclofenac (41%) and 5-Fluorouracil (11%), in OTRs (19).…”
Section: Discussionmentioning
confidence: 99%
“…About this, there are data supporting the use of PDT in the treatment of AKs in OTRs; and a recent clinical trial compares PDT with IMI 5%, showing a higher efficacy of PDT (17,18). In a recent review, PDT shows the highest rates of complete clearance (40-76.4%), followed by IMI 5% (27.5-62.1%), diclofenac (41%) and 5-Fluorouracil (11%), in OTRs (19).…”
Section: Discussionmentioning
confidence: 99%
“…A recent extensive systematic review by Heppt and colleagues (not included in the table as no meta‐analysis done) concluded that MAL‐cPDT has the most data and highest clearance rates of AK in SOTR of any treatment studied.…”
Section: Review Of Photodynamic Therapy Outcomes In Solid Organ Transmentioning
confidence: 99%
“…Although the goals of AK treatment in organ transplant recipients (OTRs) do not generally differ from those in immunocompetent patients, it is important to consider that some treatments may be less effective or have a different safety profile in OTRs as a result of their immune‐related mechanism of action. Considering the large number of OTRs and other people who are chronically immunosuppressed, the interesting and comprehensive systematic review included in this issue of the BJD is of great value.…”
mentioning
confidence: 99%
“…In their systematic assessment of evidence from randomized trials of treatments for AKs in OTRs, Heppt et al . found that photodynamic therapy was the intervention most frequently investigated and associated with the highest rates of complete clearance and reduction in lesion counts.…”
mentioning
confidence: 99%
See 1 more Smart Citation